2022
DOI: 10.1093/humrep/deac107.456
|View full text |Cite
|
Sign up to set email alerts
|

P-485 The TurnerFertility study: data on fertility preservation (FP) by ovarian tissue cryopreservation (OTC) in young girls with Turner syndrome (TS)

Abstract: Study question Which girls with TS could benefit from FP by OTC, based on the presence of follicles in relation to karyotype, clinical and hormonal data? Summary answer Girls with TS who have favourable predictive parameters (e.g 46,XX cell line, a measurable AMH or spontaneous puberty) could benefit from FP by OTC. What is known already Infertility due to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Currently, several attempts including cryopreservation of ovarian tissues of prepubertal girls are made to preserve fertility of these women (11). Fleischer et al reported that ovarian tissue cryopreservation was helpful for fertility preservation in women with Turner syndrome who have favorable predictive parameters such as 46,XX cell lines and spontaneous puberty (46). Further studies using ovarian tissue samples will serve to improve the reproductive outcomes in women with Turner syndrome.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Currently, several attempts including cryopreservation of ovarian tissues of prepubertal girls are made to preserve fertility of these women (11). Fleischer et al reported that ovarian tissue cryopreservation was helpful for fertility preservation in women with Turner syndrome who have favorable predictive parameters such as 46,XX cell lines and spontaneous puberty (46). Further studies using ovarian tissue samples will serve to improve the reproductive outcomes in women with Turner syndrome.…”
Section: Future Perspectivesmentioning
confidence: 99%